EFFECT OF SOLAR DEHYDRATION METHOD ON PHYSICO-CHEMICAL AND SENSORY CHARACTERISTICS OF GREEN BEANS (PHASEOLUS VULGARIS) - Priyanka, Kuna; Chandni, R.C.; Sankar, Amar; Raghu, A.V. (International Journal of Research -GRANTHAALAYAH, 2017)
Studies were done by different chemical treatments under solar dehydration of Green beans. The Green beans were treated by five different methods which are mentioned and the end product was underwent analysis for physico-chemical characteristics, nutritional characteristics, microbial analysis and sensory evaluation. Five treatments of different proportions with Magnesium chloride, Sodium chloride, Sodium bicarbonate and Magnesium oxide were done for solar dehydration of Green beans and (0.1% Magnesium chloride and 0.1% Sodium bicarbonate) treated Green beans were found to be good in all characteristics i.e. Physico-chemical (better chlorophyll retention) and nutritional characteristics when compared to other treatments.